Re-evaluating winter carbon sink in Southern Ocean by recovering MODIS-Aqua chlorophyll-a product at high solar zenith angles - Zhang, Ke; Zhang, Zhaoru; He, Jianfeng; Smith, Walker O.; Liu, Na; Le, Chengfeng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)
Satellite ocean color observations are extensively utilized in global carbon sink evaluation. However, the valid coverage of chlorophyll-a concentration (Chla, mg m−3) measurements from these observations is severely limited during autumn and winter in high latitude oceans. The high solar zenith angle (SZA) stands as one of the primary contributors to the reduced quality of Chla products in the high-latitude Southern Ocean during these seasons. This study addresses this challenge by employing a random forest-based regression ensemble (RFRE) method to enhance the quality of Moderate Resolution Imaging Spectroradiometer (MODIS) Chla products affected by high SZA conditions. The RFRE model incorporates the color index (CI), band-ratio index (R), SZA, sensor zenith angle (senz), and Rayleigh-corrected reflectance at 869 nm (Rrc(869)) as predictors. The results indicate that the RFRE model significantly increased the MODIS observed Chla coverage (1.03 to 3.24 times) in high-latitude Southern Ocean regions to the quality of standard Chla products. By applying the recovered Chla to re-evaluate the carbon sink in South Ocean, results showed that the Southern Ocean’s ability to absorb carbon dioxide (CO2) in winter has been underestimated (5.9–18.6 Tg C year−1) in previous assessments. This study underscores the significance of improving the Chla products for a more accurate estimation of winter carbon sink in the Southern Ocean.
Keywords: Sørishavet; fjernmåling; fotogrammetri; karbon syklus; karbondioksid; oseanografi

Is, fly og skip : oppdagelse og kartlegning med fly i Øst-Antarktis 1929-1939 - Widerøe, Turi; Drivenes, Einar-Arne (Universitetet i Tromsø, 2006)
Keywords: Antarktis; ekspedisjoner; fly; fotogrammetri; geografi; historie; hvalfangst; kartlegging; kartografi; oppdagelsesreiser

Satellittkartlegging ved Norsk Polarinstitutt - Amlien, Jostein (Kart og plan, 1989)
Keywords: Dronning Maud Land; fotogrammetri; kartlegging; kartografi; satellite bilder